1993
DOI: 10.1111/j.1600-051x.1993.tb01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin in the gingival crevice as a marker of polymorphonuclear leucocytes in periodontal diseases

Abstract: This study examined lactoferrin (LF) levels in gingival crevicular fluid (GCF) and set out to test the hypothesis that LF could act as a marker of crevicular polymorphonuclear leucocytes (PMN). Therefore, 2 experiments were conducted: (a) to quantify total LF (ng/30 s sample) in GCF; (b) to correlate LF levels (ng/microliters) and PMN numbers (PMNs/microliters) in gingival crevicular washings (GCW). GCF was collected from 71 sites in a total of 22 patients. These sites were classified on the basis of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 30 publications
6
50
0
Order By: Relevance
“…This illustrates that the increase in the chronic periodontitis severity affects the concentration of lactoferrin in gingival crevicular fluid. These results are in accordance with the opinion of Adonogianaki et al 14 and Ozdemir et al 19 that there are different levels of lactoferrin in GCF significantly between patients with gingivitis and periodontitis compared with healthy subjects. Tsai et al 8 also revealed that there is a strong relationship between periodontal clinical parameters with levels of lactoferrin.…”
supporting
confidence: 82%
“…This illustrates that the increase in the chronic periodontitis severity affects the concentration of lactoferrin in gingival crevicular fluid. These results are in accordance with the opinion of Adonogianaki et al 14 and Ozdemir et al 19 that there are different levels of lactoferrin in GCF significantly between patients with gingivitis and periodontitis compared with healthy subjects. Tsai et al 8 also revealed that there is a strong relationship between periodontal clinical parameters with levels of lactoferrin.…”
supporting
confidence: 82%
“…Another study indicated that the hLF level in GCF correlates with the clinical severity of periodontal diseases and the number of polymorphonuclear leucocytes (Adonogianaki et al 1993). A decrease in hLF levels was observed in GCF and saliva after surgical periodontal treatment in chronic periodontitis (Jentsch et al 2004), and in GCF and peripheral blood after oral hygiene procedures in experimental gingivitis using healthy volunteers (Ozdemir et al 2009).…”
Section: Lf As a Marker Of Periodontal Diseasesmentioning
confidence: 96%
“…The antibacterial properties of lactoferrin are due to its high affinity for iron, thus locking available sources required for bacterial growth. Lactoferrin showed better correlation with clinical indices than PMNs (Adonogianaki et al, 1993). Friedman et al (1983) found that lactoferrin increased twofold in GCF in sites showing gingivitis, periodontitis, and localized juvenile periodontitis.…”
Section: Lactoferrinmentioning
confidence: 97%